2020
DOI: 10.1097/wnr.0000000000001386
|View full text |Cite
|
Sign up to set email alerts
|

Selenium nanoparticles reduce glucose metabolism and promote apoptosis of glioma cells through reactive oxygen species-dependent manner

Abstract: Gliomas are the most common, malignant, and lethal tumors in adults. Furthermore, gliomas are highly resistant to current chemotherapeutic drugs. Thus, new effective anticancer drugs for glioma are urgently needed. Selenium nanoparticles have been reported to have potent anti-tumor activity, although the specific mechanism is not fully understood. This study aimed to test the anti-tumor effect of selenium nanoparticles and its mechanism. We used selenium nanoparticles to treat commercial glioma cell lines, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…Other laboratory studies confirmed similar results in glioblastoma treatment with some modifications in surface decorating ligands for Se nanoparticles like HER2 and arginylglycylaspartic acid (You et al, 2016;Jardim et al, 2017;Song et al, 2018). Also, it has been demonstrated that Se-containing nanoparticles treatment significantly reduced both the bioenergy metabolism and the invasion of drug-resistant glioma cells (Xu B. et al, 2020), while benign cells remained viable indicating that Se toxicity is selective for glioma cells.…”
Section: Selenium-containing Nanotreatment Of Glioblastomasupporting
confidence: 61%
“…Other laboratory studies confirmed similar results in glioblastoma treatment with some modifications in surface decorating ligands for Se nanoparticles like HER2 and arginylglycylaspartic acid (You et al, 2016;Jardim et al, 2017;Song et al, 2018). Also, it has been demonstrated that Se-containing nanoparticles treatment significantly reduced both the bioenergy metabolism and the invasion of drug-resistant glioma cells (Xu B. et al, 2020), while benign cells remained viable indicating that Se toxicity is selective for glioma cells.…”
Section: Selenium-containing Nanotreatment Of Glioblastomasupporting
confidence: 61%
“…First, the decoration of nanoparticles by sialic acids can enhance their delivery to tumor cells and therapeutic efficacy. The recent study by Xu et al confirmed the strong apoptotic action of selenium nanocarriers against glioma cells [ 75 ]. However, their modification by sialic acid significantly increases the uptake by malignant cells and potentiates the apoptotic effect.…”
Section: Theranostic Aspect Of the Use Of Nanoparticles (Nps) In Gliomamentioning
confidence: 95%
“…• In vitro: Selenium NP (Xu et al, 2020), MNP (Shen et al, 2017) • In vivo: MP (Cheng Y. et al, 2016;Kim et al, 2010)…”
Section: Standalone Therapy Preclinicalunclassified
“…2019; Shi et al, 2019;Sousa et al, 2019;Ye et al, 2019;Zhang et al, 2019;Zhao et al, 2019;ZhuGe et al, 2019;Alves et al, 2020;Caban-Toktas et al, 2020;Chung et al, 2020;Ferreira et al, 2020;Kazmi et al, 2020;Liang et al, 2020;Martinez-Rovira et al, 2020;Meng et al, 2020;Roberts et al, 2020;Ullah et al, 2020;Wang H. et al, 2020;Wang X. et al, 2020;Xu et al, 2020;Zhu et al, 2020; see Table 3 for examples of ligand targeting in glioma research). Another active targeting method to increase functional specificity of NPs that are used as gene delivery systems is the transcriptional targeting, which can occur at a transcriptional or posttranscriptional level (Golombek et al, 2018).…”
Section: Radiotherapy Enhancermentioning
confidence: 99%
See 1 more Smart Citation